The Benefits of Physical Activity to Reduce Mortality in Postmenopausal Breast Cancer Patients: A Literature Review - Thomas Jaya Gumilang; Budi Hernawan (Indonesian Journal of Cancer, 2023)
Background: Breast cancer cases are more commonly diagnosed in postmenopausal women and the risk increases with age. Along with an increased vulnerability to breast cancer, increasing age also carries a higher risk of other health problems. Postmenopausal breast cancer patients frequently have one or more pre-existing comorbid conditions at the time of diagnosis. Higher physical activity can reduce breast cancer-specific and overall mortality. However, the vast majority of early breast cancer survivors experience a decrease in physical activity. This study aimed to determine the relationship between physical activity and the reduction of Breast Cancer-Specific Mortality (BCSM) and overall mortality in postmenopausal breast cancer survivors.Methods: This research uses a literature review design by conducting a journal search through Google Scholar, PubMed, and ScienceDirect. The keywords used are (“Physical activity” or Exercise) and (“Breast Cancer” or “Breast Neoplasm”) and (Mortality) and (“Post-menopause”).Results: Seven studies were included in this review. A total of 6276 deaths were reported. Only 3 out of 6 studies reported that there is a significant benefit between physical activity and reduction in breast cancer-specific mortality. Contrarily, all studies reported that there is a significant benefit between physical activity and overall mortality reduction, but at a certain intensity level. Conclusions: Our data suggest that physical activity, whether pre-diagnosis or post-diagnosis, is associated with a better prognosis of breast cancer in postmenopausal women.